SOSIALISASI PENGURANGAN SAMPAH PLASTIK AIR MINUM MENINGKATAN PENGETAHUAN, SIKAP, DAN PERILAKU MAHASISWA DALAM PENGGUNAAN TUMBLER - Nasution, Andreanda; Septiana, Henni Rizki; Sukriah, Sukriah (Poltekkes Kemenkes Bandung, 2023)
The issue of plastic bottle waste in Indonesia remains unresolved as of this writing. This study aimed to find out how students' knowledge, attitudes and behavior change regarding tumbler use after socialization regarding reducing plastic waste in drinking water. A pre-experimental design using a one-group pretest-posttest design model was the study design that was employed. This activity uses an intervention or outreach approach to address plastic bottle waste, stress the value of drinking water, and encourage the usage of tumblers. The activity was carried out offline targeting first semester FIKES UIKA students. The sample in this study was 67 respondents using a cluster random sampling technique. The tool used in this study was a questionnaire. A paired T test was used to test the difference of each variable after treatment with socialization. The respondents with good knowledge increased to 82.1% compared to only 71.6% during the pre-test. Attitudes incre The issue of plastic bottle waste in Indonesia remains unresolved as of this writing. This study aimed to find out how students' knowledge, attitudes and behavior change regarding tumbler use after socialization regarding reducing plastic waste in drinking water. A pre-experimental design using a one-group pretest-posttest design model was the study design that was employed. This activity uses an intervention or outreach approach to address plastic bottle waste, stress the value of drinking water, and encourage the usage of tumblers. The activity was carried out offline targeting first semester FIKES UIKA students. The sample in this study was 67 respondents using a cluster random sampling technique. The tool used in this study was a questionnaire. A paired T test was used to test the difference of each variable after treatment with socialization. The respondents with good knowledge increased to 82.1% compared to only 71.6% during the pre-test. Attitudes increased with respondents who had positive attitudes increasing at the post-test by 98.5% compared to only 40.3% at the pre-test. In the behavioral variable, there was also an increase in good behavior during the post test by 68.7% compared to only 31.3% during the pre test. The results of the study showed that there were differences in students' knowledge, attitudes and behavior regarding the use of tumbler after being given intervention in the form of socialization, with p-values of 0.020, 0.000 and 0.000 respectively. In conclusion, socialization had a significant impact on respondents' knowledge, attitudes and behavior regarding the use of tumbler. ased with respondents who had positive attitudes increasing at the post-test by 98.5% compared to only 40.3% at the pre-test. In the behavioral variable, there was also an increase in good behavior during the post test by 68.7% compared to only 31.3% during the pre test. The results of the study showed that there were differences in students' knowledge, attitudes and behavior regarding the use of tumbler after being given intervention in the form of socialization, with p-values of 0.020, 0.000 and 0.000 respectively. In conclusion, socialization had a significant impact on respondents' knowledge, attitudes and behavior regarding the use of tumbler.